Photoinduzierte Cycloeliminierung konjugierter 5,6-Epoxy-triene der Jononreihe - A.P. Alder; H.R. Wolf; O. Jeger (CHIMIA)
UV-irradiation (λ = 254 nm; pentane) of the epoxy-triene 3 gives the isomers 4 (35 %), 5 (40 %) and 6 (5 %). The dihydrofurane 4 is the product of a thermal electrocyclization of the ylide a. On the other hand, a undergoes fragmentation to give the carbenoids b and c. Intramolecular addition of the carbene in b yields 6, whereas an analogous process in c gives 5. UV-irradiation (λ = 254 nm; pentane) of the epoxytriene 7 yields the isomers 8 (60%), 9 (25%) and 10 (ca. 5%). The tricyclic ketones 8 and 9 are products of an intermediate cyclopropene compound 11. 11 and the isomeric cyclopropene 10 are cyclization products of carbenoids (b' → 10; c' → 11) formed by fragmentation of an ylide a' (a' → b'; a' → c').